Economic Hardship, Ocular Complications, and Poor Self-reported Visual Function are Predictors of Mental Problems in Patients with Uveitis. (18th August 2021) - Jin, Yingying; Lin, Dan; Dai, Ma-Li; Liu, Ruru; Jiang, Mengxi; Zheng, Jingwei; Yang, Yi-Mai; Zhu, Xue-Fei; Wang, Yu-Lin; Huang, Xiu-Feng; Wang, Yuqin
ABSTRACT: Purpose : To characterize the quality of life and mental health status of patients with uveitis and investigate predictors of psychological problems. Methods : A total of 245 patients and 105 controls were enrolled in this cross-sectional study. Quality of life, psychological status, socio-demographic and clinical data were obtained from questionnaires and medical records. Multivariate regression analyses and Receiver Operating Characteristic (ROC) were applied to obtain the model predicting psychological problems of patients. Results : Of 245 patients, 16.7% and 26.5% ( P < .0001) screened positive for anxiety and depression, respectively. The model predicting anxiety was comprised of low annual household income and poor self-reported visual function ( P = .029, P < .0001, respectively), with an AUC of ROC of 0.744. The model predicting depression was comprised of poor self-reported visual function and ocular complications ( P < .0001, P = .012, respectively), with an AUC of 0.78. Conclusions : Economic hardship, ocular complications, and poor self-reported visual function are predictors of mental problems in patients with uveitis.